Literature Study: Implementation of Good Corporate Governance (GCG) in State-Owned Company PT Bank Mandiri Tbk. - Panjaitan, Gloria; Tamba, Rani; Maisyarah, Renny (Indonesian Journal Publisher, 2025)
This study aims to examine the application of Good Corporate Governance (GCG) principles at PT Bank Mandiri (Persero) Tbk as one of Indonesia's government-owned banks. The implementation of GCG is believed to be able to improve company performance through effective risk control and create trust from various stakeholders, including the public, investors, and the government. Bank Mandiri has won various awards for GCG implementation, including the title of